#### Answer

$-1$

#### Work Step by Step

Step 1: $i=\sqrt {-1}$
Step 2: $(i)^{2}=(\sqrt {-1})^{2}$
Step 3: Therefore, $i^{2}=-1$.

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-1$

Step 1: $i=\sqrt {-1}$
Step 2: $(i)^{2}=(\sqrt {-1})^{2}$
Step 3: Therefore, $i^{2}=-1$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.